Music, language, and meaning in Nigerian highlife: a communicative analysis of “So Ala Temem” - Ẹ̀jẹ̀bá Salem Ǒchála; Bolaji, David (Linguistik Online, 2026)
This study examines Cardinal Rex Lawson’s (1969) “So Ala Temem” as a multidimensional communicative event in which language, music, and sociocultural meaning intersect. Highlife music provides a lens to analyze how melodic, rhythmic, and performative elements convey both referential and affective content. The study draws on a high-fidelity recording, researcher-generated transcription, and consultations with native Kalabari, Ibani, Izon, and Okrika speakers. An interdisciplinary approach combines ethnographic linguistics, musicological analysis, and sociocultural interpretation, guided by Highlife scholarship, musilanguage theory, and Hymes’ (1974) SPEAKING model. Findings show that “So Ala Temem” goes beyond entertainment, integrating multilingual elements and playful vocalisations (ludic or vocable-based sound) with instrumental and vocal techniques to create a musilinguistic synthesis. The interplay of language and music reinforces social cohesion, moral guidance, and communal identity. Melodic phrasing, rhythmic patterns, and expressive vocalizations encode cultural knowledge and affective meaning, while repetition, interjections, and chorused refrains structure the song and enhance audience engagement. Lawson’s performance exemplifies the communicative and cultural significance of Nigerian Highlife, demonstrating how musical and linguistic strategies convey ethical instruction, social norms, and collective memory.